Modeling the impact of floating offshore wind turbines on marine food webs in the Gulf of Lion, France - Adgé, Mathieu; Lobry, Jérémy; Tessier, Anne; Planes, Serge (Frontiers in Marine Science, 2024)
A trophic model was developed to predict the potential impacts of a future commercial floating wind farm in the Golf of Lion, on the ecosystem, by studying the evolution of biomass and ecological network indicators (ENA). Four scenarios were designed in order to simulate 1/ the "reef effect" caused by the new hard substrate created by the wind farm structure, 2/ the association of the reef effect with the reserve effect caused by the closure of the wind farm to fishing, 3/ the impact of regular harvesting of sessile organisms from the hard substrate by fishermen and, 4/ the impact of the transfer of these organisms to the seafloor. Our study suggests changes in the ecosystem structure and functioning after the introduction of a wind farm, where low trophic level groups became more important in the functioning of the trophic web, the ecosystem maturity decreased, and the overall activity and diversity increased. The biomass of some pelagic and demersal groups increased. Overall, the introduction of large wind farm platforms will transform the local ecosystem, enhancing the overall production which will likely provide benefits to local fisheries focused on higher trophic level groups.